The Return of Martin Guerre - Önal, Muhsin (Muş Alparslan Üniversitesi, 2015)
In this work we want to explain some of the important developments in historiography that mark the last decades. The strating point of this work is the book of Natalie Zemon Davis “The Return of Martin Guerre.” This is the story of what happened in the sixteenth century French town of Artigat and it deals with rural peasant life. The book is Davis’ interpretation of the events in which there some blank areas that needed filling in with assumptions, well founded as they might be. Her work is after all a scholarly endeavor where there is very little description of the scenery and the appearance of the people. In Davis’ book truth seems to be the more important value that she is trying to get at and she gives the feeling in the book version of the story that the characters are more interested in truth than anything else. It appears that truth and identity are the motifs of the book.

losophically unpersuasive, a rhetorical device not a scientific proof. The second problem which arises from the use of detailed example to illustrate mentalité is how to distinguish the normal from the eccentric. The third problem concerns interpretation if the historian succeed to get inside the past man head the narrator will need all the skill and experience and knowledge acquired in the practice of analytical history of society, economy and culture (Stone, L., 1981: 94, 95)
Book Review/ Kitap Değerlendirme “The Return of Martın Guerre”
anemon